Combined Immunoscore for Prognostic Stratification of Early Stage Non-Small-Cell Lung Cancer - Boscolo, Alice; Fortarezza, Francesco; Lunardi, Francesca; Comacchio, Giovanni; Urso, Loredana; Frega, Stefano; Menis, Jessica; Bonanno, Laura; Guarneri, Valentina; Rea, Federico; Conte, PierFranco; Calabrese, Fiorella; et al. (Frontiers in Oncology, 2020)
Background To date, no combined immunoscore has been evaluated for prognostic stratification of early stage non-small-cell lung cancer (NSCLC). The main goal of this study was to investigate the prognostic impact of programmed death ligand 1 (PD-L1) expression and different immune cell components (CD4+, CD8+ T-lymphocytes, and CD68+ macrophages) in early stage NSCLC patients, distinguishing peritumoral (PT) and intratumoral (IT) localizations. The secondary aim was to identify a combined immunoscore to optimize the prognostic stratification of NSCLC patients. Methods This retrospective study included surgical specimens from consecutive chemo-naive stage II–III radically resected NSCLC patients. Immunohistochemistry was carried out to evaluate PD-L1 expression and to quantify IT and PT CD4+, CD8+ T-lymphocytes, and CD68+ macrophages. The impact of a single marker and of a combination of multiple markers on overall survival (OS) was investigated. Results Seventy-nine patients were included in the study. PD-L1 expression was associated with worse prognosis (3 years OS: 58% in high- compared with 67% in low-expressing tumors), even though without statistical significance. When integrating PT CD8+, CD4+, and CD68 into a combined PT immunoscore, a significant prognostic stratification of patients was obtained and confirmed at multivariate analysis (3 years OS: 86% in patients with low PT immunoscore vs. 59% in patients with high PT immunoscore, p = 0.018). The integration of derived neutrophil/lymphocyte ratio (dNLR) with combined PT immunoscore improved prognostic stratification, with longer OS in patients with low PT immunoscore and low dNLR (p = 0.002). Conclusion The combined PT immunoscore (CD8+, CD4+, and CD68) integrated with dNLR may be a promising marker for the development of an integrated Tumor, Node, Metastasis (TNM) immunoscore.